A beautiful mind - Grazer, Brian, 1953-; Howard, Ron.; Goldsman, Akiva; Crowe, Russell, 1964-; Harris, Ed, 1950-; Connelly, Jennifer; Bettany, Paul, 1971-; Goldberg, Adam, 1970-; Hirsch, Judd.; Lucas, Josh.; Rapp, Anthony; Plummer, Christopher; et al. (Universal City, CA : Universal, 2002)
Dramatic biography of John Nash, a mathematical genius, who made an astonishing discovery early in his career and stood on the brink of international acclaim. But the handsome and arrogant Nash soon found himself on a painful and harrowing journey of self-discovery. After many years of struggle, he eventually triumphed over his schizophrenia, and finally, late in life, received the Nobel Prize.
Based on the novel by Sylvia Nasar.
Special features: Disc 1 - feature film; deleted scenes - with optional director's commentary ; Disc 2 - A Beautiful Partnership: Ron Howard and Brain Grazer; development of the screenplay; meeting John Nash - The Nash Theory of Equilibrium; "Accepting the Nobel Prize in Economics"; "The Process of Age Progression"; storyboards to final feature comparison; creation of special effects; scoring the film; inside A Beautiful Mind; Academy Awards: Best Picture, Best Director, Best Supporting Actress, Best Adapted Screenplay; A Beautiful Mind soundtrack.
Director of photography, Roger Deakins ; art director, Robert Guerra ; editors, Mike Hill, Dan Hanley ; music composer, James Horner ; costume designer, Rita Ryack ; production designer, Wynn Thomas.
Russell Crowe, Ed Harris, Jennifer Connelly, Paul Bettany, Adam Goldberg, Judd Hirsch, Josh Lucas, Anthony Rapp, Christopher Plummer.
MPAA rating: PG-13.
DVD, Dolby digital 5.1, Dolby digital 2.0 surround.
Keywords: Nash, John F., -- Jr., -- 1928-2015 -- Drama; Mathematicians -- United States -- Drama; Feature films